Matrix Metalloproteinase -9 and Tissue Inhibitors of Metalloproteinasr-1 and -2 as Potential Novel Biomakers in Gestational Hypertension - Ab Hamid, Jabrullah (2010)
Gestational hypertension (GH) is a common disorder during pregnancy, which could progress to preeclampsia (PE) and even causing various subsequent maternal and perinatal complications. A cluster of enzymes called matrix metalloproteinase (MMP) and tissue inhibitors of metalloproteinase (TIMP) are thought to be involved in the pathophysiology of the disease. The purpose of this study was to determine the circulating (serum) levels of the MMP-9, TIMP-1 and TIMP-2 in GH patients and compare with normotensive pregnant women as well as to correlate the pregnancy outcomes, such as preterm delivery, poor progress, foetal distress, mode of delivery, low birth weight, small for gestational age, low apgar score, meconium-stained liquor and neonatal intensive care unit admission. A total of 118 patients were randomly selected in this unmatched case-control study. Subjects include GH women (n=54) and controls (n=64) were healthy normotensive pregnant women, selected from those who have attended the outpatient clinics at General Hopital Kuala Lumpur and Serdang Hospital during May 2008 to January 2009 and fulfilled the specified selection criteria. All the patients were followed up until delivery, all desired patients’ information and the outcomes of the pregnancies were gathered from medical records. The levels of each biomarker were measured by using specific Enzyme-Link Immunosorbent Assay (ELISA) technique and the MMP/TIMPs ratios were calculated manually. MMP-9 was found slightly higher in the GH group (p=0.085). In the subgroup analysis based on parity, MMP-9 and MMP-9/TIMP-1 ratio were slightly higher in nulliparous GH group (p=0.064 and p=0.079 respectively), and TIMP-1 was slight higher in multiparous GH group (p=0.062). However all these findings do not reach statistical significance at p=0.05. A weak positive correlation (statistically significant) was found between maternal age and TIMP-1 in GH group (r=0.278, p=0.047). Similarly, a weak positive correlation (statistically significant) was found between gestational age and TIMP-2 in control group (r=0.318, p=0.010). There is no correlation found between MMP and TIMPs with blood pressure levels. Pre-eclampsia developed in 8 (15%) GH women. The rate of low birth weight (p=0.040), small for gestational age / intra-uterine growth restriction (p=0.018), meconium-stained liquor (p=0.018) and Neonatal Intensive Care Unit admission (p=0.001) were significantly increased in GH group. Although the rate of poor progress, caesarean sections, instrumental deliveries, low APGAR score and neonatal jaundice were increased in GH, they were not statistically significant (p>0.05). Preterm delivery rate was not significantly different between GH and normotensive pregnancy. Even though lacking in statistical significance, a higher level of MMP-9 was found in the GH group. Similarly comparisons made based on parity were noted to be lower, approaching statistical significance, especially in the nulliparous subgroup. This could also be a sign of the increased risk of PE and GH in nulliparous pregnancy. The different patterns of MMP-9 and TIMP-1 and -2 alterations between nulliparous and multiparous women could also suggest different underlying pathophysiological changes between the two subgroups. The analysis comparing pregnancy outcomes between the two groups showed increased risk for various adverse outcomes as well as maternal and perinatal complications among GH women.